2008
DOI: 10.1007/s12020-008-9111-9
|View full text |Cite
|
Sign up to set email alerts
|

Human uncoupling protein 2 and 3 genes are associated with obesity in Japanese

Abstract: Human uncoupling proteins (UCPs) are mitochondrial proteins that are involved in the control of energy metabolism and the pathophysiology of obesity. Although there have been several reports on the association between the UCP2/UCP3 locus and the obesity, there have been no haplotype-based case-control studies with gender-specific analysis. The aim of this study was to examine whether there is an association between the UCP2/UCP3 locus and the obesity in the Japanese population when using a single nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
12
0
2
Order By: Relevance
“…Regarding the association between UCP3 -55C/T and BMI, the present study's findings are in accord with the previous studies conducted on Japanese (Hamada et al, 2008;Matsunaga et al, 2009). It has also been reported that, in addition to the association with UCP3 -55C/ T, there were associations of haplotypes (H5 and H6) of this polymorphism with UCP2 A55V and UCP3 rs2075577 (Kosuge et al, 2008). Again, reasons for discrepancies in outcomes may be attributed to the heterogeneity in these studies settings such differences in sample size, and participants' inclusion criteria, such as age, gender, and obesity status.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the association between UCP3 -55C/T and BMI, the present study's findings are in accord with the previous studies conducted on Japanese (Hamada et al, 2008;Matsunaga et al, 2009). It has also been reported that, in addition to the association with UCP3 -55C/ T, there were associations of haplotypes (H5 and H6) of this polymorphism with UCP2 A55V and UCP3 rs2075577 (Kosuge et al, 2008). Again, reasons for discrepancies in outcomes may be attributed to the heterogeneity in these studies settings such differences in sample size, and participants' inclusion criteria, such as age, gender, and obesity status.…”
supporting
confidence: 92%
“…Several studies have reported, though discrepantly, the association of obesity with UCP single-nucleotide polymorphisms (SNPs), including UCP1 -3826A/G (rs1800592) (Nakano et al, 2006;Jia et al, 2010), UCP2 -55 A/V (rs660339), a 45bp insertion-deletion polymorphism in the UCP2 gene (UCP2 I/D) (rs1800795), and UCP3 -55C/T (rs1800849) (Shiinoki et al, 1999;Hamada et al, 2008;Kosuge et al, 2008;Jia et al, 2009;Matsunaga et al, 2009). However, studies on the association between these SNPs and intervention-induced weight loss are few and, except for UCP1 -3826A/G (Nagai et al, 2011), none of these studies was conducted on Japanese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, A55V was significantly associated with obesity in men of Japanese. The frequency of subjects with the AV or VV types in the obese group was 67.4%, which was significantly lower than the frequency observed in the nonobese group (78.1%) [14]. Another report showed that G-866A was associated with a reduction in the prevalence of type 1 diabetes in Germany [15].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that more than 1 billion adults worldwide are overweight, 300 million of whom are clinically obese—defined as having a body mass index (BMI) equal to or greater than 30 kg m −2 , or a waist circumference greater than 94 cm for men and 80 cm for women [2]. Obesity is a chronic, multifactorial, and complex disease resulting from a long-term positive energy balance, in which both genetic and environmental factors are involved [3, 4]. It was recently suggested that some forms of obesity are associated with chronic low-grade inflammation [5].…”
Section: Introductionmentioning
confidence: 99%